Budesonide + formoterol delivered via Spiromax® for the management of asthma and COPD: The potential impact on unscheduled healthcare costs of improving inhalation technique compared with Turbuhaler®. (August 2017) - Lewis, A.; Torvinen, S.; Dekhuijzen, P.N.R.; Chrystyn, H.; Melani, A.; Zöllner, Y.; Kolbe, K.; Watson, A.T.; Blackney, M.; Plich, A.
Abstract: Background: Fixed-dose combinations of inhaled corticosteroids and long-acting β2 agonists are commonly used for the treatment of asthma and COPD. However, the most frequently prescribed dry powder inhaler delivering this medicine – Symbicort ® (budesonide and formoterol, BF) Turbuhaler ® – is associated with poor inhalation technique, which can lead to poor disease control and high disease management costs. A recent study showed that patients make fewer inhaler errors when using the novel DuoResp ® (BF) Spiromax ® inhaler, compared with BF Turbuhaler ® . Therefore switching patients from BF Turbuhaler ® to BF Spiromax ® could improve inhalation technique, and potentially lead to better disease control and healthcare cost savings. Methods: A model was developed to estimate the budget impact of reducing poor inhalation technique by switching asthma and COPD patients from BF Turbuhaler ® to BF Spiromax ® over three years in Germany, Italy, Sweden and the UK. The model estimated changes to the number, and associated cost, of unscheduled healthcare events. The model considered two scenarios: in Scenario 1, all patients were immediately switched from BF Turbuhaler ® to BF Spiromax ® ; in Scenario 2, 4%, 8% and 12% of patients were switched in years 1, 2 and 3 of the model, respectively. Results: In Scenario 1, per patient cost savings amounted to €60.10, €49.67, €94.14 and €38.20 in Germany, Italy, Sweden and the UK, respectively. Total cost savings in each country were €100.86 million, €19.42 million, €36.65 million and €15.44 million over three years, respectively, with an estimated 597, 754, 151, 480, 228, 986 and 122, 368 healthcare events avoided. In Scenario 2, cost savings totalled €8.07 million, €1.55 million, €2.93 million and €1.23 million over three years, respectively, with 47, 850, 12, 118, 18, 319, and 9789 healthcare events avoided. Savings per patient were €4.81, €3.97, €7.53 and €3.06. Conclusions: We demonstrated that reductions in poor inhalation technique by switching patients from BF Turbuhaler ® to BF Spiromax ® are likely to improve patients' disease control and generate considerable cost savings through healthcare events avoided. Highlights: An economic analysis of poor inhalation technique with asthma and COPD inhalers. Switching patients from BF Turbuhaler ® to BF Spiromax ® may reduce inhaler errors. Cost savings from fewer inhaler errors may reach €15–100 million over 3 years.